Efektivitas Media Sosial Tiktok Terhadap Personal Branding Ganjar Pranowo Pada Masyarakat Jawa Tengah: indonesia - Adina indri lestari; Nanda nia rahayu; Rani setiawati (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
Tiktok is a social media platform that is currently loved by the public and is used for various purposes such as seeking information, as a means of entertainment, selling, looking for product recommendations, online shopping features, and can even be a means of building and improving one's self-image (personal branding) through uploads, comments, and the information provided therein. As one example, the political figure of the community, Hanjar Pranowo, made TikTok a place to develop one's personal branding. The purpose of this study is to determine the impact of the social media platform TikTok on Ganjar Pranowo's personal branding among the people of Central Java. Survey research is a type of research conducted. The positivist paradigm is the paradigm used in this study, and a descriptive quantitative approach to the research was taken as a result. In this study survey research was conducted by sending questionnaires to Generation Z of Central Java via Google Form. The personal branding idea popularized by Peter Montoya is used in this study. The results of this study show that the effectiveness of social media TikTok has an impact of 74.7% on Ganjar Pranowo's personal brand. The conclusion from the results of this study is that 0.000 has a significant effect, and the results of the t-test and t-table test were found by researchers, namely T-number > T-table 12.972 > 2.001, namely the influence of the social media variable TikTok (X) and personal branding among Ganjar Pranowo for the people of Central Java.Keywords: Ganjar Pranowo, Communication Effectiveness, PersonalÂ Branding.